Dimensões da biblioteca escolar no ensino fundamental School library dimensions at the basic education p. 46-53 - Ely, Neiva Helena (Revista ACB, 2005)
Considera aspectos da biblioteca escolar e do bibliotecário escolar.Apresenta as dimensões social, informativa, pedagógica, recreativa e criativa dabiblioteca escolar no ensino fundamental. Abstract: Considers aspects of school library and school librarían. Presents social,informative, pedagogie, recreative and creative dimensions of school library inbasic Learning. Keywords: School library; School librarian; School library - Basic Learning –Dimensions